Eksistensi Kecerdasan Buatan dalam sebagai Subjek Hukum: Kajian Holistik Berdasarkan Perspektif Filsafat Hukum Eksistensialis - Rasji; Akhirudin (CV Rewang Rencang, 2024)
The development of artificial intelligence, becoming increasingly complex, has sparked profound debates regarding its legal status, particularly whether AI can be considered a legal subject. To address this issue, this study adopts an existentialist philosophical approach, focusing on the concepts of freedom, consciousness, and responsibility as the fundamental elements of human existence. The research employs a qualitative approach with a philosophical analysis of the concepts of subjectivity and existence, drawing on the ideas of prominent existential thinkers such as Jean-Paul Sartre and Martin Heidegger. The findings indicate that although AI is capable of independent action and mimicking decision-making processes similar to humans, it lacks self-consciousness and existential freedom—traits that are inherently human. Therefore, from an existentialist perspective, AI does not meet the criteria to be regarded as a legal subject, as it does not possess authentic existence or the moral responsibility associated with legal subjects. Based on these findings, it can be concluded that the legal status of AI is more appropriately viewed as an object of law, requiring special regulation, rather than as an entity with legal rights and obligations akin to humans.